Gym cafe healthy food - Ahmad Tarmizi, Ahmad Aiman (Universiti Teknologi MARA, Perak, 2023)
Gym Cafe is a cafe that modifies its concept. Originally the cafe was just a shop that served coffee. Later it was converted into a cafe with a gym bar concept. Moreover, the menu is based on a healthy eating style. The gym cafe is positioned near the center of the gymnasium. This is to encourage the customers, especially bodybuilders, to visit the cafe. Operating hours are from 7am to 10pm.